Biochemical characterization of mt‐PemIK, a novel toxin‐antitoxin system in Mycobacterium tuberculosis. Issue 24 (10th November 2018) - Chi, Xiaodong; Chang, Yunqing; Li, Mengmiao; Lin, Jin; Liu, Yi; Li, Chuanyou; Tang, Shenjie; Zhang, Junjie
Abstract : Toxin‐antitoxin (TA) systems are regarded as genetic modules that facilitate bacterial survival under stress conditions. In this study, a novel TA system in Mycobacterium tuberculosis H37Rv chromosome was identified, termed as mt‐PemIK, which consists of antitoxin mt‐PemI and toxin mt‐PemK (Rv3098A). Induction of mt‐PemK leads to growth arrest in Mycobacterium smegmatis, while the toxic effect of mt‐PemK is eliminated by co‐expression of mt‐PemI. mt‐PemK is characterized as an endoribonuclease whose activity is pH‐dependent. mt‐PemK, as well as some other M. tuberculosis toxin/antitoxin proteins, can be modified by pupylation, suggesting that the Pup‐proteasome system is involved in the regulation of TA systems. These results are helpful to understand the mechanisms of M. tuberculosis growth regulation under stress conditions. Abstract :